2018
DOI: 10.1080/17461391.2018.1424942
|View full text |Cite
|
Sign up to set email alerts
|

Sodium bicarbonate ingestion increases glycolytic contribution and improves performance during simulated taekwondo combat

Abstract: NaHCO ingestion was able to increase the contribution of glycolytic metabolism and, therefore, improve performance during simulated taekwondo combat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
75
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(91 citation statements)
references
References 55 publications
(91 reference statements)
13
75
2
1
Order By: Relevance
“…Likewise, it is strongly argued that acidosis does not inhibit contractile machinery and that alkalization may cause instability of the buffering systems, and thus, the benefit to the ATP-generating process is either negligible, or actually harmful (Korzeniewski and Zoladz 2002; Sahlin et al 1998). A recent study by Lopes-Silva et al (2018), nonetheless, reported similar post-exercise HCO 3 − and lactate responses to the current study following NaHCO 3 ingestion, yet also reported both a 34% greater estimated glycolytic energy contribution to exercise and an improved performance. It is alternately conceivable that the increases in HCO 3 − and CO 2 following NaHCO 3 ingestion are part of a causal sequence of the primary mechanism of performance, by accelerating V O 2 kinetics at the onset of high-power outputs (Zoladz et al 2005).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Likewise, it is strongly argued that acidosis does not inhibit contractile machinery and that alkalization may cause instability of the buffering systems, and thus, the benefit to the ATP-generating process is either negligible, or actually harmful (Korzeniewski and Zoladz 2002; Sahlin et al 1998). A recent study by Lopes-Silva et al (2018), nonetheless, reported similar post-exercise HCO 3 − and lactate responses to the current study following NaHCO 3 ingestion, yet also reported both a 34% greater estimated glycolytic energy contribution to exercise and an improved performance. It is alternately conceivable that the increases in HCO 3 − and CO 2 following NaHCO 3 ingestion are part of a causal sequence of the primary mechanism of performance, by accelerating V O 2 kinetics at the onset of high-power outputs (Zoladz et al 2005).…”
Section: Discussionsupporting
confidence: 80%
“…The change in HCO 3 − during TT 1 was increased following NaHCO 3 (SBC2 + 29%, SBC3 + 34%), whilst post TT 1 , blood lactate was also greater compared to PLA (SBC2 + 21%, SBC3 + 23%). These changes suggest an increased H + buffering from intramuscular to extracellular compartments, which may lead to an increased anaerobic energy provision and glycogen utilization, as intramuscular pH is better protected (Lopes-Silva et al 2018; Percival et al 2015). It is argued that these indirect biomarkers of upregulated glycolytic flux in the present study instead show a reduction in lactate by inactive tissue however, as the samples in the present study do provide data on use/uptake (Granier et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…This assumption was supported by the higher [HCO 3 − ] and BE values pre-and post-PTSR in the bicarbonate group compared with the control group, but the lack of any significant difference in exercise-induced difference between pre-and post-PTSR values. Recent studies reported an increased glycolytic energy contribution to exercise and improved anaerobic exercise performance following NaHCO 3 ingestion under normoxic [70] and acute hypoxic conditions [16]. It has also been suggested that changes in blood pH and [HCO 3 − ] are greater during exercise with NaHCO 3 ingestion and the associated elevation of pre-exercise [HCO 3 − ] and BE values, which is supposed to explain the increased anaerobic exercise performance in acute hypoxic conditions following NaHCO 3 ingestion [19].…”
Section: Discussionmentioning
confidence: 99%
“…Despite difficulties in validating the PCr+glycolysis measure, it has been used in a variety of activities, including rock climbing (Bertuzzi et al, 2007), martial arts (Lopes-Silva et al, 2018), and table tennis test (Zagatto and Gobatto, 2012). However, it has been validated for only one of these activities.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the widespread use of the PCr+glycolysis measure, including its application to a variety of exercise modes, such as rock climbing (Bertuzzi et al, 2007), a variety of martial arts, such as taekwondo (e.g., Lopes-Silva et al, 2018), table tennis (Zagatto and Gobatto, 2012), and rowing (de Campos Mello et al, 2009), we felt it important to confirm its validity. In running, metabolic demand is a function of body mass and it is customary to report measures of aerobic and anaerobic fitness (e.g., VO2max and maximal accumulated oxygen deficit) relative to mass.…”
Section: Introductionmentioning
confidence: 99%